Equity valuation of SolarCity - Pedro, André Pereira (2016)
In this research note, a valuation exercise of SolarCity – a solar panel manufacturer and supplier – is presented. SolarCity is a recently created company (2006), whose aim is to lower the cost of solar panels in order to allow people to follow a “greener” source of energy. This company was founded by Peter and Lyndon River, with the financial and marketing push given by their cousin, Elon Musk, when he participated in the first round of financing. SolarCity only operates in some states of the USA, being fully vertically integrated it is present from the manufacture until the maintenance of the already installed solar systems, which renders a huge advantage in relation to its competitors. In the valuation exercise the DCF model was applied along with the WACC discount rate, which seemed the most appropriate model to value the company given the available information and its capital structure. A relative valuation was then constructed, along with an EVA model in order to compare and validate the results obtained in the DCF. A target price of $36.50 per share was thus reached for SolarCity. Subsequently, a comparison with a major investment bank research note was performed in order to compare the methodology used and the final target price - JP Morgan Research note, performed on the 23rd February 2016. In the end, a Hold recommendation criterion for the stock was reached. This does not consider the stock to be undervalued, because of the industry where it operates and the good growth perspectives.